Crohn's disease: is there a place for neurological screening? - Stovicek, Jan; Liskova, Petra; Lisy, Jiri; Hlava, Stepan; Keil, Radan (Scandinavian journal of gastroenterology, 2014)
OBJECTIVE: Neurological complications of inflammatory bowel diseases (IBDs) are not rare but are under-diagnosed; some are probably immune-mediated. Several previous studies have suggested a higher incidence of demyelinating diseases such as multiple sclerosis in IBD patients. In this single-center, prospective, observational study, the authors focus on T2 focal white-matter lesions of the central nervous system on magnetic resonance imaging (MRI) in IBD patients that may be due to demyelination. MATERIAL AND METHODS: A total of 70 patients with Crohn's disease were examined before beginning anti-TNF-α therapy. These patients were treated with azathioprine, mesalazine or both. Patients were examined by a neurologist to detect possible signs of demyelinating disease, and patients underwent brain MRI (native T1, T2, and FLAIR sequences). RESULTS: Thirty-seven patients (53%) exhibited abnormalities on neurological examination, and 26 patients (37%) displayed abnormalities on MRI. In seven cases, these MRI abnormalities (periventricular lesions) were suspected to be due to demyelination. Cerebral spinal fluid investigation (including polyclonal bands) was completely negative in five cases and was borderline in one case, and multiple sclerosis was confirmed in one case. Pathological MRI findings in 19 other patients were clinically nonsignificant; most were nonspecific sporadic lesions in white matter or mild atrophy. CONCLUSIONS: The results support previous data that the frequency of neurological findings in IBD patients is generally underestimated. With the extension of biological anti-TNF-α treatment for IBD, the possibility of a higher risk of developing multiple sclerosis should be considered.
Keywords: dospělí; Magnetic Resonance Imaging; demyelinizační nemoci; Female; Adult; Tumor Necrosis Factor-alpha; mladý dospělý; ženské pohlaví; Adolescent; lidé; Neurologic Examination; magnetická rezonanční tomografie; neurologické vyšetření; Crohn Disease; TNF-alfa; prospektivní studie; Male; Aged; Prospective Studies; Demyelinating Diseases; Young Adult; lidé středního věku; Crohnova nemoc; senioři; mužské pohlaví; Middle Aged; mladiství; Humans